Atitudes do locutor no discurso na perspectiva da teoria da argumentação na língua - Delanoy, Cláudio Primo (2012)
On the interaction of language, the speaker expresses himself discursively, and enters in relation with other discourses. The goal of this thesis is to describe and explain the actions taken by the speaker to express his point of view in relation to others discourses, and to investigate the relation among these discourses and their meanings, under the perspective of the Theory of Argumentation within Language and the Theory of Semantic Blocks, by Oswald Ducrot, Marion Carel and collaborators. We elected these theories because they consider the meaning is built by language in the relation established among words, sentences and paragraphs, in a situation of enunciation. When expressing a point of view, the speaker assumes a particular argumentative aspect of a semantic block. In interaction with other discourse, which is also represented by an argumentative aspect, the speaker takes an attitude. Thus, our goal is to describe and explain these attitudes of the speaker, through the relation between aspects. The corpus considered for analysis consists of written discourses of various structures (fables, stories, editorials, comic strip). After the argumentation analysis, the argumentative aspects can be related to each other and thus it allows us to study the meaning built by the speakers and their attitudes.